Extended electric system cascade analysis (ESCA) for a carbon constraint energy generation system - Lee, Ming Yang (APPLIED ENERGY, 2016)
Growing concerns of energy security and environmental issues have posed a great challenge in sustainable energy planning. Renewable energy (RE) resources as well as carbon capture and storage (CCS) are the common alternatives to reduce the impact of carbon emission. However, integration of RE and CCS into the current energy system requires thorough planning. With consideration of existing power fossil based power plant, this paper aims to provide a carbon-constraint energy generation that includes optimal capacities of new power plants and energy storage to meet with the increasing energy demand by using an extended version of the Electric System Cascade Analysis (ESCA) methodology. This method is applied on an hourly scale of a hypothetical case study. The demand side is supplied by an existing 40 MW coal-fired power plant, subjected to a maximum carbon emission constraint of 850 ton CO2/day. The result reveals that additional of 15 MW of new solar photovoltaic power plant and 82 MW of new natural gas power plant with CCS are required to meet with the increasing demand under carbon constraint. The system is integrated with an energy storage of 86 MW in capacity.